2014
DOI: 10.1111/jcc4.12079
|View full text |Cite
|
Sign up to set email alerts
|

Uniting Political Bloggers in Diversity: Collective Identity and Web Activism

Abstract: In contrast to the common view of blogging as a highly narcissistic activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
1
29
0
1
Order By: Relevance
“…Social trust is built on the belief that ingroup members are more honest and trustworthy than members of outgroups (Levin, Whitener, & Cross, 2006). It has been found that social trust unites diverse participants in social movements under a collective identity of protestors (Diani 2000;Jones, 2011;Soon & Kluver, 2014). Social identification becomes even stronger when it is combined with relevant experience of the specific target (Walther et al, 2011), which is why people may tend to trust friends who have had the experience of being a protestor in the context of social movements most.…”
Section: Social Identification and Technological Affordancesmentioning
confidence: 99%
“…Social trust is built on the belief that ingroup members are more honest and trustworthy than members of outgroups (Levin, Whitener, & Cross, 2006). It has been found that social trust unites diverse participants in social movements under a collective identity of protestors (Diani 2000;Jones, 2011;Soon & Kluver, 2014). Social identification becomes even stronger when it is combined with relevant experience of the specific target (Walther et al, 2011), which is why people may tend to trust friends who have had the experience of being a protestor in the context of social movements most.…”
Section: Social Identification and Technological Affordancesmentioning
confidence: 99%
“…Those studies have generated different types of research regarding the democratic possibilities of Internet GOMES [44], SILVA [45], of how the digital interactions are constituted as proxies of the level of political participation and engagement LÉVY [46], CASTELLS [37], MAIA [47], EGLER [48], PENTEADO, Open Access Library Journal SANTOS and ARAUJO [49], EISENBERG [50], as well as collective identities formation MAIA and CASTRO [51], MITRA [52], Acklanda and O'Neila [53], LAMB e POSTER [54], SOON and KLUVER [55].…”
Section: The Trust Dimensionmentioning
confidence: 99%
“…While some research has considered the distinction between online and offline actions more generally, results are mixed. For example, Soon and Kluver () found that political blogging (commonly viewed as a ‘narcissistic activity’, p. 500) promoted the emergence of collective identity that drove collective action both online and offline. However, other research (exploring online socio‐political action more broadly) has suggested that mobilization attempts are specific to media: Face‐to‐face mobilization attempts promote offline actions, while online mobilization attempts to promote online actions (Vissers, Hooghe, Stolle, & Maheo, ; see also Brunsting & Postmes, ; Postmes & Brunsting, ).…”
Section: Social Identity Injustice and Efficacy In Kony2012mentioning
confidence: 99%